Zur Systematisierung von Planungsprozessen. Issue 3 (3rd July 2017) - Hoffmann, Anna; Oberding, Sarah
Abstract: In recent decades planning processes have been described by many authors. This article therefore proposes a systematization of planning process models. The analysis considers 30 planning processes that have been developed since the 1950s and that either originate from spatial planning or can be applied to spatial processes. Systematization is carried out using analytical criteria: the course of planning process and methods. The 30 models of planning process can be divided into three main groups: classic, incremental and strategic models, although the majority fall into the classic group. The classic and strategic models are further differentiated according to the course of the planning process, i.e. into linear and circular models. Alongside the criterion course of planning process, these groups are especially distinguished from one another by their use of methods. Goal finding and planning management methods are primarily proposed for use with the classic models; in contrast, methods of analysis and participation play an important role within the strategic models. The methodological approach used in the incremental models is individually developed in line with the specific situation; thus, for these models proposals for appropriate methods are usually avoided.